Activated Carbon, Carbon Blacks and Graphene Based Nanoplatelets as Active Materials for Electrochemical Double Layer Capacitors: A Comparative Study. Issue 1 (1st January 2015) - Schütter, C.; Ramirez-Castro, C.; Oljaca, M.; Passerini, S.; Winter, M.; Balducci, A.
Abstract : In this study we compare the properties and the performance of three different carbonaceous materials, namely activated carbon, carbon black and graphene based nanoplatelets, as active materials for electrochemical double layer capacitors (EDLCs). The aim of this investigation is to contribute to the assessment of the advantages and limits related to the use of alternative active carbonaceous materials for EDLCs, with particular regard to carbon blacks. The results of this investigation indicate carbon black as a very promising candidate for the realization of high performance EDLCs, able to display high energy and high power. However, float test for 500 h at 2.7 V have shown strong capacitance fade for carbon black based EDLCs. Post-mortem SEM analysis revealed cracks in the electrode surface, which could be related to the breakage of carbon black agglomerates during float test, which then in turn may be the reason of the strong capacitance fade. Overcoming this issue will be the next challenging step in order to be able to take advantage of the promising characteristics of this carbon black for longer time periods.